The effects of dietary selenium on the oxidative stress of beluga, Huso huso, fed high copper - Mohseni, M.; Sotudeh, A.M. (2013)
The effects of dietary selenium (Se) were investigated on the oxidative stress of beluga, Huso huso, fed high dietary copper (Cu). The basal diet with high Cu (50mg Cu/kg) was supplemented with low (0mg Se/kg, HCuLSe), adequate (11mg Se/kg, HCuNSe) and 5× adequate (55mg Se/kg, HCuHSe) of Seandfed to fish with initial body mean (±SD) weight 14.96 ± 1.39g for 12 weeks. Basal diets containing adequate Se (11mg Se/kg) and adequate Cu (10mg Cu/kg) were used as controls (NCuNSe). Weight gain, specific growth rate and condition factor for fish fed the HCuHSe diet was significantly lower than fish that fed the other diets. Se and Cu content was positively correlated with dietary Se and Cu concentrations. Hepatic Se concentration was higher in fish fed the HCuHSe diet than fish that fed other diets. Thiobarbituric acid-reactive substances (TBARS) were significantly lower. Whereas, Glutathione peroxidase activity activities were significantly higher in liver tissue of fish fed HCuHSediet than those fish fed other diets. Plasma total immunoglobulin concentration and lysozyme activity were higherin fish fed the NCuNSe diet, followed by fish fed the HCuNSe diet, and were lower in fish fed the HCuHSe diet. The results indicated that optimum levels of Cu and Se ingestion induced an oxidative stress in beluga and improved their immune response. High dietary Se (5×adequate) supplementation reduced the oxidative stress and depressed the immune response of the fish.